Fine-Scale Heterogeneity in Crossover Rate in the garnet-scalloped Region of the Drosophila melanogaster X Chromosome. - Singh, N.D.; Stone, E.A.; Aquadro, C.F.; Clark, A.G. (Genetics, 2013)
Homologous recombination affects myriad aspects of genome evolution, from standing levels of nucleotide diversity to the efficacy of natural selection. Rates of crossing over show marked variability at all scales surveyed, including species-, population-, and individual-level differences. Even within genomes, crossovers are nonrandomly distributed in a wide diversity of taxa. Although intra- and intergenomic heterogeneities in crossover distribution have been documented in Drosophila, the scale and degree of crossover rate heterogeneity remain unclear. In addition, the genetic features mediating this heterogeneity are unknown. Here we quantify fine-scale heterogeneity in crossover distribution in a 2.1-Mb region of the Drosophila melanogaster X chromosome by localizing crossover breakpoints in 2500 individuals, each containing a single crossover in this specific X chromosome region. We show 90-fold variation in rates of crossing over at a 5-kb scale, place this variation in the context of several aspects of genome evolution, and identify several genetic features associated with crossover rates. Our results shed new light on the scale and magnitude of crossover rate heterogeneity in D. melanogaster and highlight potential features mediating this heterogeneity.